Philosophia Translata: The Development of Latin Philosophical Vocabulary through Translation from Greek : A Case Study Approach - Dowson, Christopher J. (Mnemosyne, Supplements, 2023)
How Latin philosophical vocabulary developed through the translation of Greek sources, the varieties of translation practices Roman philosophers favoured, and how these practices evolved over time are the overarching themes of this monograph. A first of its kind, this comparative study analyzes the creation of philosophical vocabulary in Lucretius, Cicero, Apuleius, Calcidius, and Boethius. It highlights a Latin literary tradition in which the dominance of Greek philosophical expression was challenged and renovated over time through the individual translation choices of different Latin authors. Included are full glossaries of Latin and Greek philosophical terms with explanatory notes for the reader.